Comparative Study of Ibuprofen Solubility in Synthetic and Natural Lipid Vehicles - Roni, Monzurul Amin; Jalil, Reza-ul (Dhaka University Journal of Pharmaceutical Sciences, 2012)
DOI: http://dx.doi.org/10.3329/dujps.v10i1.10018 DUJPS 2011; 10(1): 65-66